TEORI HARMONI PENGANTAR KAJIAN SASTRA BERBASIS KONSTITUSI - Salam, Aprinus (Paramasastra, 2017)
Literary studies can not be separated from the literary theory initiated and developed by ?Western? scholars. Indonesian Literature also refers to these theories in interpreting and explaining literary works. This paper intends to ask the historical contextuality and the theoretical independence of Indonesian literature as a nation that has a historicity different from the West. The main offer in this paper is the importance of a theory called the theory of harmony-constitution. The important objectives of the theoretical point of view of the theory of harmony-the constitution are 1) all efforts to build an independent society and social justice, 2) a happy and safe condition, and hence the freedom that has been achieved should always encourage unity, sovereignty and prosperity, and 3) the acknowledgment ?on the blessings of almighty God and by the noble driven.? Methodologically, the theory of harmony-constitution is based on semantics. This theory can be used to analyze social and cultural issues, but in the case of this paper will be tested to study literary works, especially the poetry of Chairil Anwar.